Chromosomal analysis of three Brazilian "eleutherodactyline" frogs (Anura: Terrarana), with suggestion of a new species - Siqueira, Sérgio; Aguiar Jr., Odair; Strüssmann, Christine; Del-Grande, Maria Lúcia; Recco-Pimentel, Shirlei Maria (Zootaxa, 2008)
The karyotypes of four Brazilian “eleutherodactyline” samples were analyzed aiming to provide additional cytogenetic data for future understanding of the evolutionary and systematic relationships of this large anuran group. The populations consisted of Pristimantis dundeei (Chapada dos Guimarães and Rondonópolis, Mato Grosso), Pristimantis aff. dundeei (Aripuanã, Mato Grosso) and Ischnocnema paulodutrai (Ilhéus, Bahia). The data revealed that P. dundeei and P. aff. dundeei have 2n=28 chromosomes, whereas I. paulodutrai has 2n=30. All pairs of chromosomes were telocentric, except for the subtelocentric pair 4 in I. paulodutrai. Differences in Ag-NOR pattern and interstitial heterochromatin positions clearly distinguished P. aff. dundeei from P. dundeei, and differentiated them from I. paulodutrai. The specimens of I. paulodutrai showed two distinct color patterns, but they did not differ in their cytogenetic characteristics. Karyotypes with 2n=28 and 2n=30 chromosomes have not been previously described for Brazilian “eleutherodactylines” which, to date, had been characterized as 2n=20, 2n=22 and 2n=34. The NOR position differences identified between P. dundeei and P. aff. dundeei, allied to their known distinct behavior and ecological data, suggested that the P. aff. dundeei from the Aripuanã sampling location is a new species. Similarities between I. paulodutrai and species currently assigned to Pristimantis are herein discussed on the basis of chromosome number and morphological characteristics.